Sustainable Development of Energy Supply Planning For Productive Economy in Isolated Island - Moristanto Moristanto; Guntur Tri Setiandanu (The Journal of Indonesia Sustainable Development Planning, 2020)
This paper describes the sustainable development of energy supply planning for productive economy in border, small, and isolated island using case study in the region of Sitaro Island, North Sulawesi. This paper describes that energy supply planning must be sufficient, secure, reliable, and affordable for users by using local potency of energy resources that are renewable and unlimited. The paper identifies local energy potential demand of energy, current productive economy, current system of electricity, and infrastructure of energy. It finds that the local potential of energy resources is photovoltaic. The demand of energy of Islands is primary for lighting, ironing, and entertainment. The existing economy of islands is dominated by fisheries, agriculture, and tourism. The total of electricity generated is about 6.000 kW that is all supplied using PLTD. The infrastructure of energy is covered by PLN using 4 system of distributions that are System of Siau, System of Makalehi, System of Tagulandang dan System of Biaro. The local government is concerning to build up industrial cluster of fisheries for domestic and abroad markets and also to create the exotics tourism. With a serious commitment and high awareness among government, industries, and society, it is possible to increase the economy and social welfare because they have enough energy potential, abundant fish in the sea, and good tourism prospect in the future. It concludes that the energy supply should meet the demand sufficiently, securely, reliably, and affordably. In terms of productive economy, the energy should create the value added in society and increase the welfare. It recommends that in the border, small, and isolated island, the abundant and renewable of energy resources, photovoltaic, can be substituted to PLTD. Since it is only available in daylight. In order to make it useful in midnight, we need a power storage as a back up of energy resources.